2013
DOI: 10.1111/dom.12097
|View full text |Cite
|
Sign up to set email alerts
|

Superior glycaemic control with once‐daily insulin degludec/insulin aspart versus insulin glargine in Japanese adults with type 2 diabetes inadequately controlled with oral drugs: a randomized, controlled phase 3 trial

Abstract: Aims: This phase 3, 26-week, open-label, treat-to-target trial investigated the efficacy and safety of insulin degludec/insulin aspart (IDegAsp) in insulin-naïve Japanese adults with type 2 diabetes. Methods:Subjects were randomized to once-daily injections of IDegAsp (n = 147) or insulin glargine (IGlar) (n = 149), both ±≤2 oral antidiabetic treatments. IDegAsp was given before the largest meal at the discretion of each subject (and maintained throughout the trial); IGlar was dosed according to label. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
175
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(187 citation statements)
references
References 15 publications
8
175
1
3
Order By: Relevance
“…The strategy of using a limited number of mealtime injections with basal insulin in T2DM has been well investigated in recent years [52][53][54]. In the current study series, once-daily IDegAsp gave, as expected, superior performance to IGlar alone in insulin-naïve people, without detriment in terms of hypoglycemia despite the improved postmain-meal glucose control [44]. Here, the finding by continuous glucose monitoring of lower glycemic excursions during the night appears to be consistent with the clamp findings of low within-day variability compared with IGlar [42].…”
Section: Expert Commentarysupporting
confidence: 60%
See 2 more Smart Citations
“…The strategy of using a limited number of mealtime injections with basal insulin in T2DM has been well investigated in recent years [52][53][54]. In the current study series, once-daily IDegAsp gave, as expected, superior performance to IGlar alone in insulin-naïve people, without detriment in terms of hypoglycemia despite the improved postmain-meal glucose control [44]. Here, the finding by continuous glucose monitoring of lower glycemic excursions during the night appears to be consistent with the clamp findings of low within-day variability compared with IGlar [42].…”
Section: Expert Commentarysupporting
confidence: 60%
“…In this trial, despite identical mean insulin doses, IDegAsp was superior to IGlar in lowering HbA 1c , having a clinically relevant treatment difference of −0.28 (95% CI −0.46, −0.10), with similar FPG (Table 2). Central estimates for any-time and nocturnal hypoglycemia were lower but not statistically significantly different (Table 2) [44]. Bodyweight change and adverse-event profiles were similar.…”
Section: Phase 3 Clinical Trialsmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, better glycemic control could have been achieved in the IDegAsp group if this study had been extended until fasting blood glucose reached the target value. Another phase 3 treat‐to‐target trial of once‐daily IDegAsp therapy for 26 weeks in insulin‐naïve Japanese patients showed that IDegAsp provided superior long‐term glycemic control compared with IGlar, with a similar fasting plasma glucose level and insulin dose16. However, postprandial hypoglycemia would be expected to occur if we continued to titrate the dose of IDegAsp based on SMBG data before breakfast alone, because the postprandial plasma glucose level was decreased to the fasting plasma glucose range in the IDegAsp group (Figure 3b).…”
Section: Discussionmentioning
confidence: 99%
“…It was calculated that a sample size of 20 patients was required to detect a decrease of prandial glucose corresponding to that reported in a phase 3 trial16 with a 5% level of significance (two‐sided) and a power of 80%.…”
Section: Methodsmentioning
confidence: 99%